Literature Review on Tennis-Based Physical Education Learnin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study is a literature review aimed at analyzing the effectiveness of tennis-based physical education learning in a school context. The literature search was conducted through the Scopus, PubMed, Web of Science, Google Scholar, DOAJ, SINTA, and Garuda databases, spanning 2015–2025. A total of 70 articles were identified, 35 articles were screened through titles and abstracts, and 15 articles met the eligibility criteria for analysis using the PRISMA approach. Thematic analysis was used to group the findings based on motor skills, tactical understanding, learning motivation, equipment modifications, and curriculum relevance. The review results indicate that game-based learning models such as Teaching Games for Understanding (TGfU) and game-based learning consistently improve students' coordination skills, decision-making, physical engagement, and interest. Equipment modifications such as mini-tennis and foam balls have been shown to significantly facilitate the learning process, especially in schools with limited facilities. In general, tennis is an effective, flexible, and suitable sport for implementation in modern physical education learning. However, gaps were found in the lack of research in the Indonesian context and the minimal integration of technology in learning. This review recommends the need for experimental research and development of innovative tennis-based learning models to improve the effectiveness of physical education learning in schools.